Application of factorial design and desirability function to develop a single analytical procedure for the determination of metals in different tissues of blue crab (Callinectes danae) - Lima, Daniel C.; Guedes, Wesley N. [UNESP]; Costaa, Vinicius C.; Amorim, Fábio A. C. (Sociedade Brasileira de Quimica (SBQ), 2018)
In this scientific work, it was developed a single analytical procedure for the sample preparation of different tissues of blue crabs using microwave-assisted digestion for the determination of Cu, Mn, Fe and Zn by fast sequential flame atomic absorption spectrometry (FS FAAS). The limits of quatification were 10.5, 1.6, 8.9 and 19.3 µg g-1 for Cu, Mn, Fe and Zn, respectively. The precision was estimated in terms of repeatability using the relative standard deviation (RSD, n = 7) 3.4% for Cu; 4.8% (Mn); 4.7% (Fe) and 4.7% (Zn) and accuracy of the procedure was confirmed by analysis of certified reference material (CRM) of oyster tissue (NIST 1566B) with concentration values of 71.3 for Cu, 18.3 for Mn, 202.5 for Fe and 1415 µg g-1 for Zn. The procedure has been applied for the determination of Cu, Mn, Fe and Zn in several blue crab samples from Cachoeira River estuary, Ilhéus, Bahia, Brazil.
Keywords: Desirability function; Effect of matrix; Factorial design; Singles analytical procedure